A socio-pragmatic analysis of lexical borrowing in a multilingual setting - Sasala, James Matseshe (Politeknik Negeri Bali, 2024)
The study investigated the influence of a speaker’s linguistic environment on lexical borrowing in Lukabaras. The main objective was to determine the socio-pragmatic function of the home and business domains on the borrowing of lexical items in Lukabaras from the Nandi language in Chepsaita Scheme. The research adopted the descriptive design. Data was collected from a sample of 36 respondents picked through purposive sampling technique. The analysis focused on borrowed forms of nouns and verbs. The findings showed that whereas the speaker’s linguistic environment pragmatically contributed to lexical borrowing, there was more borrowing in the home domain than the business domain. The study concluded that the socio-pragmatic function of the lexical borrowing was a communicative strategy to foster cross-cultural interactions in the multilingual setting.